Professional Teachers’ Capability in the Implementation of Online-Based Quality Learning in Covid 19 Pandemic Era: Analysis of Technology Infrastructure Support in Indonesia - Juharyanto Juharyanto; Achmad Sultoni; Ahamad Munjin Nasih; Azizatus Zahro’; Endah Tri Priyatni; Maulana Amirul Adha (Graduate School of Universitas Negeri Malang, 2021)
Abstract: The Covid-19 pandemic has changed teacher’s mindset and actions in carrying out learning. The technological infrastructure is a critical factor for teachers in maintaining the quality of online learning. This study aimed to describe the quality of PTC in implementing quality online learning in the Covid 19 pandemic era based on geographical setting and technological infrastructure support in Indonesia. This study used a mixing research approach to conceive 3116 respondents and 39 informants across primary schools in East Java and North Kalimantan. This study showed that 1) there are no significant differences in PTC for different geographical settings; 2) Infrastructure readiness is an important factor for the online learning implementation; 3) teacher's effort is the most important determining factor for the implementation of quality online learning; 4) the quality of the teacher's effort is largely determined by the policy strength and the community response. This study emphasized the need to strengthen and appreciate teachers' efforts in implementing quality learning.Abstrak: Pandemi Covid-19 telah mengubah pola pikir dan tindakan guru dalam melaksanakan pembelajaran. Infrastruktur teknologi merupakan faktor penting bagi guru dalam menjaga kualitas pembelajaran online. Penelitian ini bertujuan untuk mendeskripsikan kualitas PTC dalam mengimplementasikan pembelajaran online yang berkualitas di era pandemi Covid 19 berdasarkan setting geografis dan dukungan infrastruktur teknologi di Indonesia. Penelitian ini menggunakan pendekatan penelitian campuran dengan melibatkan 3116 responden dan 39 informan di SD di Jawa Timur dan Kalimantan Utara. Penelitian ini menunjukkan bahwa (1) tidak ada perbedaan PTC yang signifikan untuk setting geografis yang berbeda; (2) Kesiapan infrastruktur merupakan faktor penting dalam pelaksanaan pembelajaran online; (3) upaya guru merupakan faktor penentu terpenting bagi terselenggaranya pembelajaran online yang berkualitas; (4) kualitas upaya guru sangat ditentukan oleh kekuatan kebijakan dan respon masyarakat. Kajian ini menekankan perlunya penguatan dan apresiasi terhadap upaya guru dalam melaksanakan pembelajaran yang berkualitas.